Education as an effective strategy to promote nutritional knowledge, attitudes, and behaviors in street children - Zahra Arabbadvi; Zohreh Khoshnood; Golnaz Foroughameri; Mahboobeh Mazallahi (BMC Public Health, 2023)
Abstract Background Lack of nutritional knowledge and ineffective attitudes can complicate the problems faced by this group of street children and have significant effects on their behaviors. This study aimed to examine the effect of nutrition education on nutritional knowledge, attitudes, and behaviors of street children in Kerman in 2021. Methods This experimental study was conducted on 70 street children supported by Aftab Children Support Center in Kerman in 2021. The participants were selected using convenience sampling and were divided into two intervention and control groups using a random number table. A nutrition distance education program was implemented using an educational compact disk (CD) for the participants in the intervention group, while the children in the control group did not receive any training. The children’s nutritional knowledge, attitudes, and behaviors were assessed before and one month after the intervention using the Nutritional Behavior Questionnaire. The collected data were analyzed with SPSS software (version 22) using the chi-square test, paired and independent samples t-test, and analysis of covariance (ANCOVA). Results The results revealed a significant difference in nutritional knowledge, attitudes, and behaviors after the intervention (p < 0.001) due to the effect of the nutrition training program. Accordingly, the mean scores of the participants in the intervention group for nutritional knowledge, attitudes, and behaviors increased by 11.45, 14.80, and 6.05 units after the intervention compared to their scores before the intervention. Furthermore, the effects of the training program on the participants’ nutritional knowledge, attitudes, and behaviors were 89.6%, 91.5%, and 64.3%, respectively. Conclusion The findings of this study concluded that training based on nutrition education improved the children’s nutritional knowledge, attitudes, and behaviors. Thus, the officials in charge of promoting the health of vulnerable groups in the community need to provide the necessary facilities to implement effective training programs for street children and encourage them to participate in training programs.